Study of Some Immunological Aspects in Scabietic Patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
Scabies is an important parasitic skin disease that continues to persist all over the world. The current studywas designed to asses some immunological parameters that may be related with scabies disease Bloodsamples were collected from 60 patients (30 first infestation,30 re-infestation) with ordinary scabies and 30healthy individuals as a control group to determine the total and differential WBCs count , in addition seralevels of some immunological parameters including, C3,IgE and Indoleamine 2,3 dioxygenase (IDO). Theresults revealed that a significant increase (P?0.05) in total and differential WBCs count of patients groupscompared with healthy group , also the levels of immunoglobulin IgE and IDO showed a significant increase(P?0.05) in patients groups in comparison with healthy group . Concerning with complement components(C3) its levels observed a significant differences (P?0.05) between patients groups(first infestation and reinfestation) , also between patients and healthy group .